Development Of Insecticide Application Schedule For Management Of Flower Thrips And Pod Borer In Mungbean (Vigna radiata L.) (Bangladesh Journal of Agricultural Research, 2013)
The experiments were conducted to develop insecticide (Imidachlorpid, Imitaf 20SL at 0.5 ml/l) application schedule for the effective management of thrips and pod borer attacking mungbean during kharif-I season of 2010 and 2011. In both the years, suppression of thrips population and pod borer infestation were higher in double sprayed treatment than single spraying. Single spraying at 35 DAS (100% flowering) and 42 DAS (100% podding stage) suppressed flower infestation by thrips upto 86 and 93%, respectively, during 2010 and 100 & 96%, respectively, during 2011. Double spraying at 42 DAS (100% podding) and 49 DAS (seed developing stage) reduced more pod borer infestation as much as 81-83%. In kharif-I 2010, significantly the highest yield (1798 kg/ha) and MBCR (4.67) were obtained from the plots sprayed twice with Imidachlorpid at 42 DAS (100% podding) and 49 DAS (seed developing stage) but in kharif-I 2011, significantly the highest yield (1457 kg/ha) and MBCR (5.75) were obtained from the plots sprayed twice with Imidachlorpid at 35 DAS (100% flowering) and 42 DAS (100% podding stage). The double spray schedule appeared to be more effective than single spraying against pod borer. But single spray at 42 DAS (100% podding stage) appeared as more effective against flower thrips. Bangladesh J. Agril. Res. 38(1): 19-28, March 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i1.15186